Sistem Pendukung Keputusan Untuk Pemilihan Siswa Berprestasi Dengan Metode Analytical Hierarchy Process (AHP) Dan Technique For Order Of Preference By Similarity To Ideal Solution (TOPSIS) - Akhmad Luthfi Rahman; Muhammad Hasbi; Setiyowati Setiyowati (Jurnal Ilmiah SINUS, 2020)
SMA Negeri 7 Surakarta in an effort to improve student achievement by giving rewards to students who have the best performance. The selection process for SMA N 7 still uses a manual process so it is not objective, and takes a long time.So we need an application that can support the process of selecting high achieving students in SMA N 7 Surakarta, an application that can help to make decisions about the selection of high achieving students by changing the value of standard criteria into numbers. Then the right method is the AHP (Analytical Hierarchy Process) Method while for ranking with the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method. Because this method is able to produce effective, objective and efficient decisions. The system development uses the waterfall model, the system design used is object oriented approach, Use Case Diagram, Activitv, Squence Diagram, Class Diagram. The programming languages used are PHP and MySQL. Supporting software used is Notepad ++ and XAMPP as a virtual server. Testing programs using BlackBox Testing. The results of this study are Student Achievement Decision Application with the calculation of Analytical Hierarchy Process and Technique For Order Of Preference By Similarity To Ideal Solution methods.